THAYER PRODUCT AND ITS EVALUATION IN THE ACCOUNT - N.Sh.Esanmurodova; I.B.Sapayev; D.R.Omonov; O’.A.O’skanova; P.M.Yeshimbetov; S.Sh.Sovutov; Sh.Sh.Dehqonboyev (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Finished products are the final product of the production process of any economic entity. Finished products are items and products that do not require further processing at this enterprise, fully meet the standards and technical conditions, have been accepted by the technical control department (TNB) or a special commission and delivered to the warehouse of the enterprise or accepted by the customer.